Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) pada Lingkungan Sekolah - Reviandani, Oktarizka; Nirawati, Lia (Jurnal Bisnis Indonesia, 2024)
The purpose of holding Community Service is realizing a clean and healthy lifestyle for children atSDN Muneng Kidul and Muneng Leres 3 as well as children at Tunas Abadi Kindergarten. The targetwas 60 students from SDN Muneng Kidul and SDN Muneng Leres 3 Classes IV, V and VI as well as30 children from Kindergarten class A and B in Probolinggo District, Sumberasih District. Themethod used is guidance activities in the form of lecture methods, interactive discussions, andexercises. The result of the community service activities is that there is a change in behavior patternsin students who initially ignored clean and healthy living behaviors such as washing their hands withsoap under running water, now students have started practicing these behaviors in their dailyactivities. Not only that, students have also started to get used to consuming nutritious food as a formof clean and healthy living behavior. Thus, it can be concluded that this community service activity isrunning effectively.Keywords: Clean And Healthy Behaviors; School Environment; Health Education